Recommendations for donating breastmilk to human milk banks considering the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: Discuss the recommendations for donating breastmilk to Human Milk Banks (HMB) considering the COVID-19 pandemic. Methodology: The research was carried out involving publications on HMB, donated human milk (DHM) and COVID-19 indexed in the electronic databases PubMed (US National Library of Medicine), Scientific Electronic Library Online Brazil (SciELO), Web of Science and Portal Capes. The descriptors that delimited the research were: breastfeeding, maternal breastfeeding, HMB, DHM, human milk, COVID-19, pandemic and Sars-CoV-2, in Portuguese and English. Results and discussion: As the COVID-19 virus is transmitted by respiratory droplets and the it survives for varying periods on inanimate surfaces, in this work, we observe the main measures to control the virus transmission through the DHM during the entire process of collecting, processing and distributing the human milk to the newborns in the Neonatal Intensive Care Units (NeoICU). Quality control with high hygienic and sanitary rigor of the DHM is essential, such as sterilization of materials that come into contact with breastmilk, cleaning of the environment where milking will be carried out, use of cap and mask, hand-washing with soap and water, and disposal of the first jets of milked milk. Conclusion: Donors of milked human milk must perform a screening at the HMB for evaluation and guidance before starting the human milk donation, in order to avoid the transmission of the COVID-19 virus during the entire process of collecting, processing and distributing human milk to the newborns in the NeoICU.